MicroRNAs (miRNAs): Novel potential therapeutic targets in colorectal cancer - Yang, Ying; Meng, Wen-Jian; Wang, Zi-Qiang (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the most common malignant tumor and one of the most lethal malignant tumors in the world. Despite treatment with a combination of surgery, radiotherapy, and/or systemic treatment, including chemotherapy and targeted therapy, the prognosis of patients with advanced CRC remains poor. Therefore, there is an urgent need to explore novel therapeutic strategies and targets for the treatment of CRC. MicroRNAs (miRNAs/miRs) are a class of short noncoding RNAs (approximately 22 nucleotides) involved in posttranscriptional gene expression regulation. The dysregulation of its expression is recognized as a key regulator related to the development, progression and metastasis of CRC. In recent years, a number of miRNAs have been identified as regulators of drug resistance in CRC, and some have gained attention as potential targets to overcome the drug resistance of CRC. In this review, we introduce the miRNAs and the diverse mechanisms of miRNAs in CRC and summarize the potential targeted therapies of CRC based on the miRNAs.